Application of Liquid Organic Fertilizer from Coffee (Coffea canephora) Husk Waste for Corn (Zea mays L.) Seed Germination - Farid Nur Hidayat; Fidia Fibriana; Amnan Haris (Universitas Perjuangan Tasikmalaya, 2026)
Coffee husk waste is one of the largest agro-industrial byproducts, often underutilized and contributing to environmental problems. Converting this waste into liquid organic fertilizer (LOF) offers a sustainable solution for waste management and agricultural productivity. This study aimed to evaluate the physicochemical characteristics of coffee husk LOF and its effect on corn seed germination and early growth. Fermentation was carried out anaerobically for two months using EM4 as a bioactivator and molasses as a nutrient source. The resulting LOF showed favorable properties, including a neutral pH, a sweet-acidic odor, a dark brown color, and a viscosity close to that of water, which makes it easy to apply. Nutrient analysis showed nitrogen (1.57%), phosphorus (0.14%), and potassium (0.23%), totaling 1.94%. These values indicate that the N-organic content meets the minimum requirement, while the total NPK is slightly below the Indonesian National Standard (2-6%). Application of LOF at concentrations of 0.3-0.5% (v/v) significantly accelerated germination and increased root length, while shoot height and leaf number were not significantly affected. The findings demonstrate that coffee husk waste can be transformed into LOF with acceptable quality and positive effects on early plant growth. Further optimization of fermentation conditions and nutrient enrichment is recommended to meet full quality standards and broaden its application potential in sustainable agriculture.